Predictors of drug and substance abuse among school-going adolescents living in drug hotspot in Malaysia - Ismail, Rozmi; Shafurdin, Nurul Shafini; Shukor, Md Shafiin; Mohammed Nawi, Azmawati; Abdul Manaf, Mohd Rizal; Ibrahim, Norhayati; Mohd Rasdi, Roziah; Lyndon, Novel Anak; Amit, Noh; Hassan, Siti Aishah; Hanafi, Norshafizah; Ibrahim, Fauziah; et al. (Public Library of Science, 2024)
This study explored the pressing issue of drug and substance abuse (DSA) among adolescents in drug hotspots in Malaysia. The Malaysian Anti-drug Agency (AADK) has identified 155 hotspot areas across Malaysia, of which 78 were randomly selected as the study sites. These areas were identified as having extreme drug-related activities such as drug trafficking and drug-related crimes. According to the literature, several factors influence adolescents to be involved in DSA. Therefore, understanding the risk factors in the context of Malaysian school-going adolescents is of utmost importance. The study examined, in particular, a wide range of potential predictors, including socioeconomic factors, peer influence, family dynamics, educational experiences, drug access, and community characteristics. Adolescents in the hotspot areas were selected by means of a cross-sectional survey design with a cluster sampling method. The sample comprised 3382 school-going adolescents, and the data were collected through face-to-face interviews. The logit model method with STATA software was used to analyse the data. The findings of the study revealed that school-going adolescents with disciplinary issues face a two-fold increase in the risk of becoming current drug users compared to their peers. Further, those exhibiting externalising behaviours, such as aggression and rule-breaking, also face greater odds of becoming involved in DSA. Drug pushers were identified as the most significant risk factor, with adolescents exposed to them being 46 times more likely to become current drug users. The factors of friends and family also contribute significantly to adolescent drug involvement. However, adolescents with academic-related issues may be less involved if they have the protective factor of better coping skills. These findings will contribute to efforts to mitigate drug addiction and drug-related activities, particularly in high-risk communities, as well as help policymakers and healthcare professionals develop targeted interventions and generally promote the well-being of adolescents.